Increased prevalence of hypertension in haemophilia patients - van de Putte, Dietje E. Fransen; Fischer, Kathelijn; Makris, Michael; Tait, R. Campbell; Collins, Peter W.; Meijer, Karina; Roosendaal, Goris; Chowdary, Pratima; Schutgens, Roger E. G.; Mauser-Bunschoten, Eveline P. (Thrombosis and Haemostasis, 2012)
An increased prevalence of hypertension is reported in haemophilia patients, but data from large, unbiased studies are lacking. The aim of our study was to cross-sectionally assess the prevalence of hypertension in a large cohort of 701 haemophilia patients. Blood pressure (BP) measurements performed in 386 Dutch and 315 UK haemophilia patients aged 30 years or older were analysed and compared with the general age-matched male population. Mean values of up to three BP measurements were used when available. Hypertension was defined as BP over 140/90 mmHg and/or the use of antihypertensive medication. A total of 49% of patients had severe haemophilia. Mean age was 49.8 years. The prevalence of hypertension was significantly higher in haemophilia patients (49%, 95% confidence interval [CI] 45–53) than in the general population (40%, 95% CI 37–43). The prevalence of hypertension was higher in patients with severe haemophilia than in those with non-severe disease, but similar across haemophilia types and in Dutch and UK patients. Multiple BP measurements were available for 70%.The prevalence of hypertension was similar in patients with multiple BP measurements and the complete cohort. Hypertension was not significantly associated with renal function, a history of renal bleeding or with infection with hepatitis C or HIV, but it was associated with overweight/obesity and age. In conclusion, the prevalence of hypertension is higher in haemophilia patients than in the general population. The cause of this increased prevalence is unknown. Blood pressure measurements should be part of standard care in haemophilia patients aged 30 years or older.
Keywords: Haemophilia; hypertension